Disaccharide‐Based Anionic Amphiphiles as Potent Inhibitors of Lipopolysaccharide‐Induced Inflammation. (23rd October 2018) - Borio, Alessio; Holgado, Aurora; Garate, Jose Antonio; Beyaert, Rudi; Heine, Holger; Zamyatina, Alla
Abstract: Despite significant advances made in the last decade in the understanding of molecular mechanisms of sepsis and in the development of clinically relevant therapies, sepsis remains the leading cause of mortality in intensive care units with increasing incidence worldwide. Toll‐like receptor 4 (TLR4)—a transmembrane pattern‐recognition receptor responsible for propagating the immediate immune response to Gram‐negative bacterial infection—plays a central role in the pathogenesis of sepsis and chronic inflammation‐related disorders. TLR4 is complexed with the lipopolysaccharide (LPS)‐sensing protein myeloid differentiation‐2 (MD‐2) which represents a preferred target for establishing new anti‐inflammatory treatment strategies. Herein we report the development, facile synthesis, and biological evaluation of novel disaccharide‐based TLR4⋅MD‐2 antagonists with potent anti‐endotoxic activity at micromolar concentrations. A series of synthetic anionic glycolipids entailing amide‐linked β‐ketoacyl lipid residues was prepared in a straightforward manner by using a single orthogonally protected nonreducing diglucosamine scaffold. Suppression of the LPS‐induced release of interleukin‐6 and tumor necrosis factor was monitored and confirmed in human immune cells (MNC and THP1) and mouse macrophages. Structure–activity relationship studies and molecular dynamics simulations revealed the structural basis for the high‐affinity interaction between anionic glycolipids and MD‐2, and highlighted two compounds as leads for the development of potential anti‐inflammatory therapeutics. Abstract : High‐affinity TLR4 antagonist : Synthetic 1, 1′‐β, α‐diglucosamine‐based glycolipids inhibit Gram‐negative lipopolysaccharide‐induced endotoxicity in vitro. Crystal‐structure‐based design, straightforward chemical synthesis, and biological evaluation by a variety of in vitro experiments accompanied by molecular dynamics simulations furnished anionic conformationally confined glycolipids (disaccharide Lipid A mimetics) as potential anti‐sepsis drug candidates and anti‐inflammatory therapeutics.